TÌNH HÌNH BỆNH ĐÁI THÁO ĐƯỜNG VÀ TĂNG HUYẾT ÁP Ở KHU VỰC CÓ NGUY CƠ PHƠI NHIỄM CHẤT DA CAM/DIOXIN - Trịnh, Khắc Sáu; Lê, Văn Quang; Võ, Viết Cường; Nguyễn, Ngọc Tân (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
INVESTIGATION ON DIABETES MELLITUS AND HYPERTESION DISEASES RELATING TO AGENT ORANGE/DIOXIN EXPOSURE Objectives: To analyze the situation of diabetes and hypertension in the BH study group residing around Bien Hoa airport - Dong Nai province and compare with the CM control group in Chanh My ward -Thu Dau Mot city - Binh Duong province. Methods: Retrospective cohort, cross-sectional description, statistical data. Results: 437 persons in the BH study group and 677 persons in the CM control group were aged from 18 to 69, regardless of gender, of which over 70.9% were aged 45-69, female accounted for over 68.9%, and 93.2% have resided for more than 15 years. The prevalence of diabetes in the BH study group before and after excluding other risk factors were 13.0% and 9.8%, respectively, higher than that of the CM control group (9.0% and 7.5%). Similarly, the rates of hypertension in BH group of 28.8% and 25.4% were also higher than those of the CM group (19.4% and 18.4%). Conclusion: Agent Orange/dioxin exposure in the BH study group could be one of the reasons for the increased prevalence of diabetes and hypertension, which was 1.3 times and 1.4 times higher than that of the CM control group, and higher 2.4 times and 1.3 times respectively in comparison with the general rates in Vietnam. The duration of residence and working in areas with the high risk of dioxin exposure affected the disease structure, with the prevalence of diabetes being 2.9 to 3.2 times higher, and the rate of hypertension from 1.5 to 2.1 times higher than the general rates in Vietnam.